21st century economics in the Muslim world - Musa Hitam Tun 1934- (MPH Group Publishing Sdn Bhd, 2013)
The decades following the era of colonialism has been marked by economic stagnation, political decadence illiteracy and poverty. Most of the these nations comprise the Muslim world, with a burgeoning young population numbering 60% of the total population below the age of 30. The existence of authoritarian regimes with rampant corruption only adds fuel to an already burning fire. In other words, this is a complete disaster. Such desperation gives rise to a people with a strong zeal to survive, to progress, and to change the fate of their people and their nations. Despite the continuing political problems in the Muslim world, the people continue to battle the odds. Today, after years of hardship, the Islamic Finance industry is now a billion-dollar industry, forecasted to grow to US$2.6 trillion by 2017. The Middle East, a region with a bleak prospect, is now a promising region, injecting massive sovereign wealth funds into the Muslim world. But more needs to be done. Tun Musa Hitam, through these few critical opinion pieces, seeks to encapsulate this fervour for change in the Muslim world, offers glad tidings of a booming business sector and lays down the road map for continued economic growth, a solid education structure and a confident young population ready to take on the world.